P 6 Visuomotor adaptation is impaired in Essential Tremor. (May 2022) - Bindel, L.; Mühlberg, C.; Pfeiffer, V.; Nitschke, M.F.; Müller, A.; Wegscheider, M.; Rumpf, J.J.; Zeuner, K.E.; Becktepe, J.S.; Welzel, J.; Güthe, M.; Classen, J.; et al.
Abstract : Introduction: Evidence has accumulated to support the theory that the cerebellum is crucially involved in the primary pathophysiology of Essential Tremor (ET). The cerebellum is critical for integration of sensorimotor information to create an internal model of movement using prediction errors. Neurological disorders causing cerebellar injury, such as degenerative cerebellar ataxia or cerebellar stroke, disrupt visuomotor integration and impede error-based learning. We hypothesized that cerebellar dysfunction in ET is also associated with impairment of visuomotor integration and error-based learning. Materials & Methods: To test this hypothesis, mildly to moderately affected ET patients (N=34; mean TETRAS score: 32.15 ± 13.78) and age-matched healthy controls performed a visuomotor adaptation task (Fig. 1A). The task was displayed on a PC monitor and movements were captured using a digital tablet. The experiment was divided into 3 phases (Fig. 1C): a baseline phase (BL), including simple center-to-target movements; an adaptation phase (ADP), in which a 30° visuomotor perturbation was introduced and a de-adaptation phase (DA), in which this perturbation was removed. The angle between the hand path and the center-target path, termed angular error, was calculated to assess visuomotor adaptation (Fig. 1B). Adaptation indices (AI; AI1 = ADP1 – BL2; AI2 = ADP8 – BL2; AI3 = DA1 – ADB8) were evaluated to assess the differences in angular error in each phase of the task (Fig. 2B). Covariates recorded were: clinical characteristics of ET patients, such as disease duration, alcohol responsivity, current medication, clinical measures of tremor and ataxia (as indexed by the TETRAS and SARA score), and basic motor performance as assessed by reaction and movement times. Results: AIs were significantly lower in ET patients compared to controls (Fig. 2A). No differences were found between ET patients and controls at BL or at DA, suggesting that the effects were specific to the adaptation phase. No differences in basic motor performance between groups were evident (all p>0.2), indicating that adaptation deficits in ET were not caused by impaired motor functions. In addition, there was no association between clinical parameters of ET and visuomotor adaptation abilities, suggesting that the reduced ability to adapt the motor response to the visual perturbation was unlikely to result from the tremulous movement. Conclusion: We found that visuomotor adaptation was impaired in ET, specifically in the adaptation phase. These results provide further evidence for linking ET to cerebellar dysfunction. Because the impairment was unrelated to clinical measures of tremor or ataxia and to basic motor performance, cerebellar dysfunction underlying visuomotor impairment in ET may be differentiated from the pathophysiological origin of other cerebellar diseases.